Extracting geotechnical information from seismic reflection surveys - examples from Australian coal mines - Hatherly, P.; Zhou, B.; Urosevic, Milovan; Peters, T. (Portugese Geotechnical Society, 2007)
In Australian coal mining there is wide-spread use of seismic reflection surveying to map coal scans prior to longwall mining. The intention is mainly [0 detect any geological faults that might have an impact on mine operations. Both 2D and 3D seismic surveys are shot but 3D surveys have greater resolution by virtue of the improved spatial correlation between seismic traces. When faults are detected, appropriate changes are made to mine plans. Seismic inversion is a process whereby the seismic reflection results can be analysed to determine the seismic properties of the layers of rock through which the seismic waves have passed. Seismic inversion does not deliver a unique solution and the process needs to be carefully constrained using borehole geophysical logs. Analysis of these logs also allows the geotechnical properties of the rock layers to be determined through the Geophysical Sirala Rating (GSR). Seismic inversiondelivers results in terms of acoustic impedances - the product of density and P-wave velocity. The impedances can be correlated with values of GSR and by converting the impedances to GSR, it is possible to assess the results of the seismic inversion in quantities familiar to geotechnical engineers. This paper presents results from two 3D seismic surveys in the Bowen Basin coalfields of Queensland, Australia.